Clinical and Radiological Features in CADASIL and NOTCH3-Negative Patients: A Multicenter Study from Turkey - MİDİ, İPEK (KARGER, 2014)
Background: The diversity of clinical presentation and neuroimaging findings of CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy) from different regions of the world has not yet been studied in depth. Here we investigated the variability of clinical, radiological and genetic data of 48 patients analyzed for NOTCH3 mutation in Turkey. Methods: Clinical evaluation was made according to a preformed questionnaire. Cranial neuroimaging findings were determined on the basis of T1, T2, FLAIR and proton-density magnetic resonance scans. For genetic analysis, polymerase chain reaction was performed with primers flanking exons 2-6 and 11 of NOTCH3 gene. Results:Twenty-five patients (52.1%) were diagnosed as CADASIL with NOTCH3 mutation, while 23 patients (47.9%) had no mutation (NOTCH3-negative patients). The mean age and age at stroke onset were lower in male CADASIL patients (p < 0.03). A family history of migraine (p = 0.012), stroke (p < 0.001), recurrent strokes (p = 0.020) and dementia (p = 0.012) was more common in CADASIL patients. Temporal pole involvement was more common in CADASIL patients (p = 0.004). Conclusion: It is of clinical importance to identify the heterogeneity of CADASIL from different countries due to a low correlation of clinical and radiological data with respect to NOTCH3 mutation. (C) 2014 S. Karger AG, Basel
Keywords: CADASIL; NOTCH3-negative patients; Radiological features; AUTOSOMAL-DOMINANT ARTERIOPATHY; NOTCH3 GENE-MUTATIONS; SUBCORTICAL INFARCTS; SELECT PATIENTS; SCREENING TOOL; LEUKOENCEPHALOPATHY; PATTERNS; FAMILIES; SPECTRUM; STROKE